Pre-combustion CO2 capture by hydrate formation using silica as a promoter - Abu Hassan, Mohd Hafiz (2017)
A rise of 2 oC in the Earth’s temperature is likely to occur when the concentration of CO2 in the atmosphere reaches approximately 450 ppm. CO2 emissions are closely related to the continual use of fossil fuels. In order to make fossil fuels sustainable, carbon capture & storage (CCS) is required to reduce CO2 emissions. There are three leading CO2 capture methods, namely post-combustion capture, oxy-fuel combustion and integrated gasification combined cycle (IGCC) pre-combustion capture. CO2 hydrate (CO2:6H2O) formation has been investigated as a way to capture CO2 in the IGCC conditions. The formation of hydrate in this work was experimentally investigated in an isochoric system (batch mode) inside a vertical fixed bed reactor (FBR), also known as high pressure volumetric analyser (HPVA). Standard silica gel with an average particle size of 200-500 µm, mean pore size of 5.14 nm, a pore volume of 0.64 cm3/g and a surface area of 499 m2/g was used as a porous medium. The presence of hydrate in FBR was justified by using graphic methods. The solubility of CO2 in water using Henry’s Law and the experimental pressure–time (P-t) curve were analysed to determine the formation of hydrate. Hydrate formation was confirmed when the mole fraction of CO2 dissolved in water exceeded the Henry’s Law value as well as a two-stage pressure drop in the experimental P-t curve. Initially, various sample preparation methods (methods 1, 2, 3 and 4) were studied leading to the selection of method 4 (the use of vigorous stirring) which had the highest moisture content (14.8 wt%) and the greatest water conversion to hydrate (40.5 mol%) at 275 K and 36 bar in a pure CO2 gas system. Also, high regeneration and repeatability of the results for all samples prepared by method 4 were expected as less water was occluded inside silica gel pores. Further investigations in pure CO2 gas systems highlighted the effect of type of silicas used, the importance of the type of promoters used, the concentration of promoters, experimental driving force, silica pore size, bed height and the amount of moisture content for formation of hydrate. Standard silica gel was the only silica found to show hydrate formation due to the best distribution of pore size. The high amount of bulk water inside zeolites 13X and spherical MCF-17 (21.3 and 50.8 wt% respectively) was the main reason of no hydrate formation observed. Additionally, the combined-promoters designated type T1-5 (0.01 mol% sodium dodecyl sulphate (SDS) + 5.6 mol% tetrahydrofuran (THF)) and type T3-2 (0.01 mol% SDS + 0.1 mol% tetra-butyl ammonium bromide (TBAB)) were the two best obtaining a CO2 uptake of 5.95 and 5.57 mmol of CO2 per g of H2O respectively. Ethylene glycol mono-ethyl ether (EGME; 0.1 mol%) was a good alternative to THF when combined with SDS (0.01 mol%) with a CO2 uptake of 5.45 mmol of CO2 per g of H2O for this combined-promoter designated type T1A-2. In addition, the CO2 uptake increased as ∆P increased or ∆T decreased. Moreover, mesoporous silica (silica gel) performed better than microporous silica (zeolite 13X) where the formation of hydrate by zeolite 13X was observed with minimal CO2 uptake (0.58 mmol of CO2 per g of H2O) when the bed height was reduced. Additionally, the total amount of CO2 consumed through hydrate formation increased as the amount of water inside mesoporous silica increased which was not the case for microporous silica. Furthermore, the experiments performed in the IGCC conditions (283 K and 70 bar) by employing T1-5 and T3-2 in a fuel gas mixture demonstrated low hydrate formation with a CO2 uptake of 1.5 and 1.1 mmol of CO2 per g of H2O respectively. This was expected due to the slow kinetics since CO2 molecules were competing with H2 molecules which also reduced the selectivity of CO2 molecules during hydrate formation. Hence, in reality, pure CO2 system is the best option for CCS through hydrate formation at the right operating conditions as compared to fuel gas mixture.